Thrombospondin-1 and blood pressure in 7-8-year-old children born low birth weight and small for gestational age - Marlyn Malonda; Adrian Umboh; Stefanus Gunawan (Indonesian Pediatric Society, 2017)
Background Thrombospondin-1 (TSP-1) is associated with endothelial damage, glomerular impairment, and hypertension. Low birth weight (LBW) and small for gestational age (SGA) children have higher risk of morbidity and mortality.Objective To assess for a possible association between TSP-1 level and blood pressure in children who were born low birth weight and small for gestational age.Methods We conducted a cross-sectional study from March to May 2015. Inclusion criteria were children who were born LBW and SGA in 2007-2008 at Prof. Dr. R. D. Kandou General Hospital, resided in Manado, North Sulawesi, had complete medical records, and whose parents consented to their participation. Exclusion criteria were children who were in puberty, obese, had renal disease, taking medications that affect blood pressure, or who were admitted to the hospital in the 2 weeks prior to enrollment.Â Data were analyzed using regression and simple correlation tests to assess for associations between TSP-1 and birth weight, as well as TSP-1 and blood pressure.Results Subjectsâ€™ mean TSP-1 level was 257.95 ng/dL. There was a strong negative correlation between TSP-1 and birth weight (r=-0.784; P<0.0001). In addition, there were strong positive correlations between TSP-1 level and systolic blood pressure (r=0.718; P<0.0001) as well as TSP-1 and diastolic blood pressure (r=0.670; P<0.0001).Conclusion Higher TSP-1 is associated with higher systolic and diastolic blood pressure in 7-8-year-old children who were LBW and SGA at birth. Also, TSP-1 and birth weight have a strong negative correlation.